GAMBARAN STATUS GIZI, SIKLUS MENSTRUASI, DAN POLA TIDUR PADA REMAJA DI SMKN 01 JAKARTA - susanti, Rosa; wijayanti, Wiwit (Siklus : Journal Research Midwifery Politeknik Tegal, 2023)
Adolescence is a period of transition from childhood to adulthood. Adolescents will go through a period of development to reach maturity so that further developments can be determined. During this period, female adolescents experience menstruation, which is a sign that the reproductive organs are functioning maturely. The occurrence of menstruation is caused by a combination of genital health and hormonal stimulation, which is a complex cause of hormonal abnormalities, one of which can be influenced by nutritional intake in adolescents, which can be assessed through nutritional status. Excess nutrition will cause obesity. The cause of obesity is more complex than the paradigm of energy imbalance, but various mechanisms play a role in it, including short sleep duration. The research was conducted at SMKN 01 Jakarta, from October to November 2022 with a total sample of 51 female students. The analysis of this research uses univariate analysis. The results of this study found that 1 (2%) person had poor nutritional status, 2 (3.9%) people had obesity nutritional status, 7 (13.7%) people had overweight nutritional status, and 41 (80.4%) people had normal nutrition. Age Menarche occurs in the majority of students at the age of 12; there are 23 (45.1%) as many as 29 (56.9%) people with normal cycles, and 43.1 percent are not. The sleep pattern before menstruation was that 25 (49%) were normal while 11 (21.6%) had insomnia. The first time I fell asleep was at 20.00 WIB. 2 (3.9%) and the latest at 01.00 WIB, namely 2 (3.9%), sleep satisfaction for the past month, namely 20 (39.2%), felt good while 4 (7.8%) were very poor.